Impact of Demonetization on Terrorism: Unraveling the Impacts: Demonetization and Terrorism in the Indian Economy (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The conceptual paper is based on demonetization and its impact on terrorism. As demonetisation is hottest topic currently in Indian economy. It has huge scope for research from all the dimensions and aspects. The paper is based on its influence on terror financing and fake currency in India. There are various benefits as well as drawbacks in this revolution in currency system in India but looking at the present scenario the most challenging task in front of government is the gaping chasm between our legal and illegal economy had reached an alarming state where the anti-national elements ranging from corrupt officials and tax evaders to state sponsored terrorists had a free run through India’s security system. Among others, demonetization has badly affected terror financing in the country. Underground operatives always store money in the form of big currency notes, and the most effect of demonetization is on those who had huge reserves of notes for unknown reasons or ventures.It is also a great step to curb the circulation of fake currency notes in India and those terror funding modules. This will prove as a severe blow and for a few years India will get relief from such anti social activities. The paper is focused on the insight of present and future of terrorism and its financing taking into consideration demonetization. There is a difference in long term and short term impacts because situation will be different with the increase in online transactions and awareness in people regarding digitization. Not only has the move to demonetize the higher currency note dealt a massive blow to the Kashmiri terror industry, it has also stunned the suspicious ‘human rights activists and civil society groups’ acting as apologists for terror activities who will now face a tough time in explaining the sources of their income and assets.